Sorting nexin 27 interactome in T‐lymphocytes identifies zona occludens‐2 dynamic redistribution at the immune synapse. (29th June 2017) - Tello‐Lafoz, María; Martínez‐Martínez, Gonzalo; Rodríguez‐Rodríguez, Cristina; Albar, Juan Pablo; Huse, Morgan; Gharbi, Severine; Merida, Isabel
Abstract : T Lymphocyte recognition of antigens leads to the formation of a highly organized structure termed immune synapse (IS) by analogy with the neuronals synapse. Sorting nexin 27 (SNX27) controls the endosomal traffic of PSD95, Dlg1, ZO‐1 (PDZ) domain‐interacting proteins, and its alteration is associated with impaired synaptic function and neurological diseases. In T‐lymphocytes, SNX27‐positive vesicles polarize to the IS, the identity of SNX27 interactors in these conditions nonetheless remains unknown. Here we used proteomics to analyze the SNX27 interactome purified from IS‐forming T cells, and confirmed the conserved nature of the SNX27/WASH/retromer association in hematopoietic cells. Furthermore, our comparative interactome analysis of SNX27 wild‐type and a mutant‐deficient for PDZ cargo recognition identified the epithelial cell‐cell junction protein zona occludens‐2 (ZO‐2) as an IS component. Biochemistry and microscopy approaches in T cells confirmed SNX27/ZO‐2 PDZ‐dependent interaction, and demonstrated its role controlling the dynamic localization of ZO‐2 at the IS. This study broadens our knowledge of SNX27 function in T lymphocytes, and suggests that pathways that delimit polarized structures in nervous and epithelial systems also participate in IS regulation. Abstract : The role of sorting nexin 27 (SNX27) in the recycling of PSD95, Dlg1, ZO‐1 (PDZ)‐interacting neuronal proteins has been widely studied. In T lymphocytes, SNX27 localizes to the immune synapse (IS) where its function remains poorly understood. Using a proteomic strategy, we identified SNX27 PDZ‐dependent and ‐independent interactome in IS‐forming T cells. We showed that SNX27 participates in the dynamics of zona occludens‐2 at the IS, which was not previously reported as an IS component.